Shuffling Deck of Personality: An Observational Study of Extraversion Traits while Playing Cards - Ni Gusti Ayu Purnami Luise (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Extraversion, a core trait within the Five-factor Model of personality, encompasses behavioural tendencies such as sociability, assertiveness, enthusiasm, and risk-taking. While numerous studies have explored extraversion through online games, the behavioural expression of this trait in offline group interactions remain underexplored. This study aims to describe how the facets of extraversion manifest during face-to-face gameplay using a structured behavioural observation approach. A subject was observed across two sessions of offline card games by three independent raters, with inter-rater reliability and composite score analysed to identify consistent trait expressions. The use of live, unmediated interaction allowed for the capture of rich social cues that are often muted in digital settings. Findings support the view that offline games provide a naturalistic and ecologically valid context to observe personality traits in action. This research contributes to a growing body of work advocating fir alternative methods in personality assessment, particularly in educational and group-based environments.